(untitled) (Bangladesh Journal of Microbiology, 2016)
With a previous observation of Escherichia coli growth cessation along with temperature variation within three different bacteriological culture media (nutrient agar, Luria-Bertani agar and minimal agar), current investigation further depicted on the possible growth dynamics of Escherichia coli (SUBE01) and Salmonella (SUBS01) growth and viability upon supplementation of different carbon sources (dextrose, sucrose, lactose, glycerol and tween 20) at 37°C under the aeration of 100 rpm. Viability of the tested bacterial species was assessed through the enumeration of the colony forming unit (cfu) appeared upon prescribed incubation for 12-24 hours on different agar plates consisting of the above mentioned carbon sources. Besides, to inspect the cellular phenotypic changes, morphological observations were conducted under the light microscope. Variations in bacterial growth (either growth acceleration or cessation) were further noticed through the spot tests on the agar plates. Considerable shortfalls in the culturable cells of E. coli and Salmonella spp. were noted in the minimal media separately consisting of sucrose, lactose, glycerol or tween 20 while an opposite impact of accelerated growth was noticed in the media supplied with dextrose. The data revealed a hierarchy of consequence of carbon sources as nutrient generators whereby the favourable bacterial growth and survival order of the carbon sources was estimated as dextrose > glycerol > lactose > tween 20 > sucrose. Bangladesh J Microbiol, Volume 32, Number 1-2,June-Dec 2015, pp 39-44